Aderência e satisfação a uma intervenção de gestão de casos para idosos caidores da comunidade: ensaio clínico randomizado - Janducci, Ana Luísa (Universidade Federal de São Carlos, 2022)
Introduction: One of the ways to prevent falls in older people is based on case management. Having greater knowledge about the factors that influence an older adult to obtain good adherence and positive satisfaction to an intervention facilitates the formulation of specific strategies for older adults at risk of falls. Objective: To verify the adherence and satisfaction to a multifactorial intervention based on case management in community-dwelling older people and related sociodemographic and clinical factors. Methods: This is a single center, randomized, parallel group controlled clinical trial. Community-dwelling older people and with a history of at least two falls in the last year were distributed in two groups. The Intervention Group underwent a case management involving multidimensional evaluation, explanation of the risk factors for falls identified, implementation of an intervention proposal based on the identified risks, elaboration of an individualized falls intervention plan, implementation, monitoring and review of the intervention plan. The Control Group was accompanied by a monthly phone call. All volunteers were initially evaluated in relation to sociodemographic data, general health, physical functions and mental functions. After 16 weeks, the volunteers answered two closed questionnaires about adherence or non-adherence to intervention (Intervention Group) and satisfaction with intervention (both groups). In addition, frequency of intervention, adhesion to each recommendation of the case management and satisfaction with general care were evaluated. Results: The final sample consisted of 62 older people. There was good adherence to intervention based on case management, as well as good adhesion to recommendations. In addition, the satisfaction of both groups was positive, although the Intervention Group had better score. There was influence of monthly income, general health assessment, years of schooling and mobility on adherence to intervention (Intervention Group). In addition, there was influence of number of falls on satisfaction with monitoring conducted in the Control Group. Conclusions: We conclude that clinical and sociodemographic factors can influence adherence and satisfaction of faller older people to a falls prevention program.
Adherence and satisfaction with a case management intervention for community-dwelling faller older people: a randomized clinical trial
Keywords: Cooperação e adesão ao tratamento; Satisfação do paciente; Acidentes por quedas; Gestão de riscos; Idoso; CIENCIAS DA SAUDE::SAUDE COLETIVA